Utilization of thyrosinase inhibitors from Artocarpus heterophyllus leaves as alternate for mercury in cosmetic products in the form of halal and thoyyib gel - Inggrit Tyautari; Ikhlasotul Fawaidah; Ika Isnayanti (Journal of Halal Product and Research, 2021)
Along with the times there is an increasing need from various fields including cosmetics. The use of cosmetics among the public is used to maintain healthy skin, beautify and maintain appearance. This increased demand for cosmetics has led to industrial competition so that there are many producers who take advantage of using a mixture of harmful substances in the manufacture of cosmetics. Mercury is a toxic cosmetic ingredient which has been widely circulating in the market. The impact of using mercury includes allergies, poisoning, and damage. The halalness of a product is an important thing in the life of a Muslim, the requirements for a cosmetics are said to be halal based on the origin of the constituent ingredients, processing and the process of obtaining them, while for cosmetic safety it is based on the function and impact it causes. The importance of monitoring halal cosmetic products is not only the role of the government, but also from the producers and consumers who are wise in the use and manufacture of cosmetics. Overcoming this problem is by making cosmetics from natural ingredients in the form of jackfruit leaf extract (Artocarpus hetetophyllus) as a substitute for the use of mercury by inhibiting the formation of tyrosine which produces melanin pigment which makes skin dark. This paper uses a maceration method in extracting young jackfruit leaves, then testing the phytochemicals on the leaf extract, which contains tyrosinase inhibitors which are classified as polyphenols. Furthermore, the preparation of cosmetic gel preparations was carried out, then the stability test was carried out including the organoleptic test, pH test, viscosity test, and homogeneity test to determine the reactivity of the prepared gel which could later be mass produced. The gel making with the active compound tyrosinase inhibitor from jackfruit leaves fulfills the requirements of halal cosmetics and thoyyib is shown by not using haram and dangerous substances through the action of a tyrosinase inhibitor in the form of acetocarpanone which has no side effect on the body because it is obtained from natural ingredients.